Mariano Siskind, Cosmopolitan Desires : Global Modernity and World Literature in Latin America, Evanston, Northwestern University Press, 2014, 357 páginas. - Josiowicz, Alejandra (Universidad Nacional de Quilmes, 2014)
Fil: Josiowicz, Alejandra. Rutgers University; Estados Unidos.